Encounters and Practices of Petty Trade in Northern Europe, 1820–1960
XIV, 353 p. 32 illus., 5 illus. in color.
Keywords: This open access book uncovers one important, yet forgotten, form of itinerant livelihoods, namely petty trade, more specifically how it was practiced in Northern Europe during the period 1820–1960. It investigates how traders and customers interacted in different spaces and approaches ambulatory trade as an arena of encounters by looking at everyday social practices. Petty traders often belonged to subjugated social groups, like ethnic minorities and migrants, whereas their customers belonged to the resident population. How were these mobile traders perceived and described? What goods did they peddle? How did these commodities enable and shape trading encounters? What kind of narratives can be found, and whose? These questions pertaining to daily practices on a grass-root level have not been addressed in previous research. Encounters and Practices embarks on hidden histories of survival, vulnerability, and conflict, but also discloses reciprocal relations, even friendships.